Cereal Crop Proteomics: Systemic Analysis of Crop Drought Stress Responses Towards Marker-Assisted Selection Breeding - Ghatak, Arindam; Chaturvedi, Palak; Weckwerth, Wolfram (Frontiers in Plant Science, 2017)
Sustainable crop production is the major challenge in the current global climatic condition. Drought stress is one of the most critical abiotic factors which negatively impact crop productivity. In recent years knowledge about molecular regulation has been generated to understand drought stress responses. E.g., information obtained by transcriptome analysis has enhanced our knowledge and facilitated the identification of candidate genes which can be utilized for plant breeding. On the other hand, it becomes more and more evident that the translational and posttranslational machinery and activity plays a major role in stress adaptation, especially for immediate molecular processes during stress treatment. Furthermore, the correlation of transcript and protein concentration is only weak because of the complexity of the translational and posttranslational machinery. Therefore, it is essential to measure protein levels and posttranslational protein modifications to reveal a real picture of metabolism during plant development and responses to biotic and abiotic stimuli. In this review, we survey proteomic studies to illustrate their applications in crop stress adaptation analysis with respect to productivity. Cereal crops such as Wheat, Rice, Maize, Barley Sorghum and Pearl Millet are discussed. A comparative analysis is performed between wheat and pearl millet considering differentially expressed protein candidates under drought stress in seed, root and leaf tissues.